2008
DOI: 10.3325/cmj.2008.49.722
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Postprandial Glucose Reductions with Viscous Fiber Blend Enriched Biscuits in Healthy Subjects and Patients with Diabetes Mellitus: Acute Randomized Controlled Clinical Trial

Abstract: Viscous fiber blend is a very potent and palatable soluble fiber addition to a starchy snack, which is able to reduce the glycemic response to a similar extent in both healthy participants and individuals with diabetes mellitus. Biscuits with low GI, and possibly other viscous fiber blend fortified starchy foods, may potentially be a useful replacement of high GI snack foods in the diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 39 publications
(51 reference statements)
4
61
0
2
Order By: Relevance
“…Other researchers also reported postprandial glucose reductions with fiberfortified snack foods. In this study, the addition of a soluble viscous fiber blend consisting of a proprietary fiber blend and the commercially available viscous fiber blend called PGX (PolyGlycopleX, InovoBiologic Inc., Calgary, Canada) reduced the glycemic response in both healthy individuals and participants with type 2 diabetes [17].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers also reported postprandial glucose reductions with fiberfortified snack foods. In this study, the addition of a soluble viscous fiber blend consisting of a proprietary fiber blend and the commercially available viscous fiber blend called PGX (PolyGlycopleX, InovoBiologic Inc., Calgary, Canada) reduced the glycemic response in both healthy individuals and participants with type 2 diabetes [17].…”
Section: Discussionmentioning
confidence: 99%
“…High-fiber versions of traditionally low-fiber foods have been shown to be palatable for patients with type 2 diabetes. 35 Consequently, this disease management strategy should not be particularly onerous for patients and may be easier to comply with than some other more intense lifestyle changes. The mean increase in fiber in the included studies was approximately 18 g/d.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is appropriate to be consumed by general populations. Previous study indicated that intake of low-GI biscuits able to reduce the glycaemic response to a similar extent in both healthy individuals and individuals with diabetes (Jenkins et al, 2008). The low-GI biscuit should be a component of standard diet, which is consumed in normal quantities and on regular basis by all consumers.…”
Section: Glycaemic Indexmentioning
confidence: 99%
“…The GI is the ranking (on a scale of 0-100) of different dietary carbohydrate-rich foods, depending on how fast and how high the blood glucose rises, and how quickly the body responds by bringing it back to normal after food ingestion (Jenkins et al, 2008). The food of medium GI is between 56 and 69.5, whilst the food of low GI is regarded as being 55 or less (Schuchardt et al, 2016).…”
Section: Glycaemic Indexmentioning
confidence: 99%
See 1 more Smart Citation